Neurocysticercosis: detection of IgG, IgA and IgE antibodies in cerebrospinal fluid, serum and saliva samples by ELISA with Taenia solium and Taenia crassiceps antigens - EDNÉIA CASAGRANDA BUENO; ADELAIDE JOSÉ VAZ; LUÍS DOS RAMOS MACHADO; JOSÉ ANTONIO LIVRAMENTO (Arquivos de Neuro-Psiquiatria)
We assayed samples of cerebrospinal fluid (CSF), serum and saliva from patients with neurocysticercoses, control group and individuals with other parasitoses, by ELISA with Taenia crassiceps vesicular fluid antigen (Tcra) and Taenia solium total antigen (Tso) for the detection of antibodies. The sensitivity for IgG-Tcra was 100% for CSF and serum, and 32.0% for saliva; and for IgG-Tso 100% for CSF, 80.0% for serum and 24.% for saliva. Specificity was 100% for CSF and 80.0% for serum with both antigens, and 100% for saliva with Tcra and 87.5% with Tso. The sensitivity and specificity for IgA-Tcra was, respectively, 40.0% and 100% for CSF, 36.0% and 97.1% for serum, and 4.0% and 90.0% for saliva. IgE detection showed 24.0% sensitivity and 97.1% specificity for serum, with no detection in CSF samples. The search for antibodies revealed the presence of IgG > IgA > IgE in CSF, serum and saliva samples, with IgG being present in all phases of the disease, while IgA/IgE were more frequent in the inactive form.